Centro de tecnificación deportiva para deportistas de alto rendimiento (2019)
The sports technification center for high performance athletes proposes a equipment that welcomes all the public of sports professionals to accompany them in their growth process as athletes and in this way increase the probability of success in national and international competitions, since He found a gap in the technique of athletes of multiple disciplines and although strength and resistance were superior to other athletes in the world, technique was his achilles heel. We chose the municipality of Medellín to project this building close to the Atanasio Girardot Sports Unit and to serve as complementary equipment